Significance of source rock heterogeneities: A case study of Mesoproterozoic Xiamaling Formation shale in North China - Xiaomei WANG; Shuichang ZHANG; Huajian WANG; Jin SU; Kun HE; Yu WANG; Xiaoqi WANG (Petroleum Exploration and Development, 2017)
Taking Mesoproterozoic Xiamaling Formation, Northern China as an example, the heterogeneities of source rock in different scales and hydrocarbon microscopic occurrence are studied based on observation of outcrops and observation with microscopy, and geochemical analysis. The large scale heterogeneities of source rocks are considered to be controlled by the plate movement and paleo-latitude location, while the micro-scale might be controlled by climate changes driven by the astronomical orbit. The constant existence of heterogeneities includes the differences of organic matter, debris sources and porosities. The heterogeneities of source rock should be seriously treated during the evaluation of oil and gas resources, especially the unconventional oil and gas. This kind of heterogeneous source rocks provides excellent source-reservoir assemblage of oil and gas generation, expulsion and accumulation, and new reference indexes for the economic evaluation of unconventional oil and gas. Therefore, quantitative study of the heterogeneity of source rock is of great significance for investigating formation mechanism and resource estimation of unconventional oil and gas. Key words: shale, source rock, heterogeneity, organic laminae, source-reservoir assemblage, unconventional oil and gas resources evaluation, Mesoproterozoic, Xiamaling Formation